Optimization of Non-Tax Revenue Through Monitoring and Supervision of Telecommunication Equipment and Devices - Mahadi Pardede (West Science Interdisciplinary Studies, 2025)
This investigation assesses the efficacy of the telecommunication equipment monitoring system instituted by Balai Monitor SFR Kelas I Jakarta and its implications for regulatory compliance, SDPPI certification, and the augmentation of Non-Tax State Revenue (PNBP). The research incorporates a quantitative examination of secondary data, including certification statistics and PNBP reports, alongside qualitative insights derived from stakeholder interviews. Employing statistical trend analysis and case study triangulation facilitated the validation of the findings. The results indicate a substantial increase in compliance rates among business operators, with over 200 devices certified in the period of 2023–2024, which has resulted in a remarkable growth in PNBP from Rp1.5 billion in 2023 to Rp10.5 billion in 2024. Furthermore, the study elucidates the manner in which monitoring enhances operational efficiency, bolsters industry credibility, and propels economic growth through infrastructural investments. This research emphasizes the criticality of collaborative engagement among stakeholders to ensure consistent policy enforcement. A significant innovation of this study is its demonstration of the role of advanced monitoring technologies in facilitating regulatory compliance and optimizing state revenue. The findings of this investigation offer policymakers a replicable framework to reinforce governance, augment compliance, and improve economic performance, thereby advancing Indonesia's digital transformation.